Editorial Vol.3 (Scholars' Journal, 2020)
Scholars’ Association of Nepal is a non-profit making scholarly organization established in 2018 with the mission of conducting academic discourse among the scholars from varied disciplines. It disseminates research studies, conducts workshops and seminars, and publishes articles from different disciplines. Thus, it has been a platform for the researchers and academicians across the country.It has been conducting research-oriented activities to develop the professional skills of the scholars, teachers and researchers. It aims to encourage academicians, (novice) researchers and teachers to read, write and share their research studies and ideas among teachers, trainers, researchers, policy makers, and practitioners of multidisciplinary subjects (Education, Curriculum, Psychology, English, Nepali, Mathematics, Social Studies, Population Studies, Economics, Health and Physical Education, Business, Management, Marketing, Law, History, Literature, Science, etc.) in the academic world through publication.In this third volume of Scholars’ Journal (SJ), we have included 16 articles following the rigorous processes of blind peer reviewing and editing. This volume includes the articles of novice scholars of Nepal from Education, English, Nepali, Sociology and Mathematics backgrounds. We believe that these articles will be fruitful for the coming generations of multidisciplinary practitioners in Nepal. We request to all valuable readers and scholars to contribute by writing for the upcoming issues and reading articles published in this volume.We express our sincere gratitude to all the authors for their appreciable contribution. Our gratitude goes to all reviewers, who supported the Editorial Team throughout the process. We are grateful to Scholars’ Association of Nepal for the publication of this journal.Thank you!Editorial TeamScholars’ Journal